Expected effect of environmental investment on market share of oil company - Matsuki, Y.; Bidyuk, P.I.; Danylov, V.J.; Yevtushenko, K.I. (Системні дослідження та інформаційні технології, 2015)
This research is aimed at examining a possibility of using environmental investment as an oil company’s strategy for increasing its market share. The numeric data of environmental investment and share price in oil market are analyzed with the method of econometrics [1], and then the computer simulation is carried out with the method of system dynamics [2]. Yearly data are collected between 2003 and 2011 from open information sources of 12 major oil companies in 8 countries, on their net incomes, share prices, environmental investments, social investments, the emitted amounts of 4 types of air pollutions, and the volumes of spilled oil into the oceans. Upon the results of the investigations, it is found that there is a possibility that a certain degree of environmental investment may increase the market share of a company; and, there is a possibility for strategic environmental investment, while still increasing the market share.